Performance Enhancement by Using Wet Pad in Vapor Compression Cooling System - Maki H. Zaidan; Thamir K. Ibrahim; Aadel A. R. Alkumait (Journal of Engineering and Technological Sciences, 2019)
Vapor compression cooling systems are widely used in hot and dry climates where the atmospheric temperature in summer reaches around 48 °C and the relative humidity can be below 20%. These cooling systems normally use environmentally friendly gases that do not harm the ozone layer. These systems work with high gas pressure, which consumes high energy and leads to a low coefficient of performance when compared to cooling systems that do not use an environmentally friendly gas. Theoretical and experimental studies have been conducted to find a suitable solution for the performance improvement of this type of cooling system. A possible solution is to lower the temperature of the air before it enters the condenser of the compression cooling system by passing it through a wet pad. The water evaporates due to the latent heat that is withdrawn from the wet pad. The air temperature is reduced to about 11 °C before it enters the condenser of the compression cooling system. This enhancement increases the cooling capacity of the vapor compression cycle by nearly 20% and increases the coefficient of performance by 15%, in addition to reducing the consumed electricity up to 15%. In conclusion, the proposed method of adding a wet pad can significantly enhance the performance of the vapor compression cooling system.